Edutainment Drone - Abdurrahman Ismail; Muhammad Iqkhmal Fitrey Farizal; Muhammad Shazwan Haslam; Mohd Muzaffar Zahar (Multidisciplinary Applied Research and Innovation, 2022)
Edutainment drone is a project where learning can be entertaining, especially for the beginner. The basic understanding of physics concepts of momentum, work, kinetic and potential energy, power, and Newton’s principles of motion all help understand how drones’ function. This project has few objectives to be achieved. The first is to ensure that students better understand the concept of learning and the fun of drones. Also, students can learn how the drone gets to fly at a certain height and fly as want without any problem. The drone movement can be controlled by adjusting the variable resistor. It can move up, down or tilt right or left, but there is a limit. The drone movement will move based on the pole. Students can measure how fast each motor can rotate based on LCD to make drone positions such as hover, move or down and tilt right or left.